What do we see out of the corner of our eye? The role of visual pivots and gaze anchors in sport. Issue 1 (1st January 2020) - Vater, Christian; Williams, Andrew Mark; Hossner, Ernst-Joachim
ABSTRACT: The role and importance of peripheral vision have been discussed across various sports. Yet, its functionality remains unclear and the terms employed in the literature to characterize the use of peripheral vision are not well defined. We present a review of 29 studies focusing on the use of peripheral vision in sports. We focus on the methodological approaches employed to study its use and identify the mechanisms that may underlie the effective use of peripheral vision in sport. We define key differences between 'gaze anchors' and 'visual pivots' and introduce the concept of a 'foveal spot'. All three gaze behaviors, while being characterized by a consistent, dynamically adjustable gaze location, have different functionalities. A gaze anchor is a cue-optimized position used for the monitoring of peripheral cues and avoiding the negative consequences of saccades (i.e. information suppression), especially under time pressure. A visual pivot is a distance-optimized location between relevant cues which allows athletes to optimally initiate saccades to those cues, especially if the costs of eye-movements are low. A foveal spot is primarily used for information processing via the fovea. Finally, we highlight suggestions for future research to improve our understanding of the functional differences between these gaze behaviors.